Safety Study of an Original Mesenchymal Stromal Cell Secretome-Based Medicinal Product for Spermatogenesis Restoration - A. O. Monakova; G. D. Sagaradze; V. Yu. Balabanyan; N. A. Basalova; A. A. Matichina; A. A. Matichin; K. L. Kryshen; V. S. Popov; Zh. A. Akopyan; A. Yu. Efimenko (Безопасность и риск фармакотерапии, 2024)
SCIENTIFIC RELEVANCE. Currently, there are no effective and safe medicinal products for idiopathic male infertility. Previous studies in two animal models of infertility (short-term cryptorchidism in rats and doxorubicin-induced testicular injury in mice) have shown the effectiveness of an originator medicinal product based on the mesenchymal stromal cell (MSC) secretome.AIM. The aim of the study was to evaluate the toxicity profile of the MSC secretome-based medicinal product in rats after local intratesticular or intramuscular administration.MATERIALS AND METHODS. The MSC secretome is a combination of factors secreted by MSCs in low-glucose Dulbecco’s modified Eagle’s medium (DMEM-LG) for MSC conditioning. In the single-dose toxicity study, the MSC secretome-based medicinal product was injected under the testicular tunica albuginea of male Wistar rats (15 per group) at doses of 15 and 25 relative units (RU) per animal, which are 1.5 and 2.5 times higher than the therapeutic dose (10 RU). In the repeat-dose toxicity study, male Wistar rats (10 per group) received intramuscular thigh injections of the medicinal product on days 1, 6, and 12 at doses of 15 and 25 RU per animal. The local tolerance study involved histopathological examination of the testes and thighs at the injection site. All studies included control groups of intact animals and animals similarly injected with blank DMEM-LG. The early follow-up period was 14 days, and the late follow-up period was 42 days.RESULTS. The rats showed no changes in the general condition after single and repeated doses of the MSC secretome-based medicinal product. Single subtunical doses induced moderate irritation; its signs included pathological changes in individual seminiferous tubules: epithelial atrophy (70% of the animals on day 14; 55% at late follow-up) and sperm stasis (70% of the animals). Similar changes were observed in the blank DMEM-LG group (up to 80% of the animals). There were no pathological changes in the tissues after repeated injections. A transient increase in alkaline phosphatase activity was detected in animals after their third intramuscular injection at a dose of 25 RU; the other biochemical parameters were normal in all study groups.CONCLUSIONS. The MSC secretome-based medicinal product has a favourable safety profile following both intratesticular and intramuscular administration, as it does not cause any permanent changes in the studied organs and tissues.